Shattered stories: Healing and reconciliation in the South African context - Wielenga, Cori (Verbum et ecclesia, 2013)
Sharing our stories has been described, by those in the field as well as by popular opinion, as a way to foster healing and reconciliation following violent conflict. This article argues that sharing stories is in itself not necessarily helpful. It is when our stories are shattered by the story of another that meaningful change can begin to take place and new stories can emerge. This idea will be explored in the South African context, with reference to the Truth and Reconciliation Commission as well as current events. It will consider storytelling and reconciliation using John Lederach’s four-part model of justice, truth, mercy and peace.